KEANEKARAGAMAN SERANGGA PADA TIGA TIPE VEGETASI DI BLOK LAMBOSIR TAMAN NASIONAL GUNUNG CIREMAI - Karyaningsih, Ika; Sonya Maalaysali Haqq, Melia; Hendrayana, Yayan; Nurlaila, Ai (Forestry Study Program University Of Mataram, 2024)
This study aims to determine the diversity of insects and their role in 3 different land covers, namely mixed forest, shrubs and calliandra vegetation in the Lambosir Block area of Gunung Ciremai National Park. This research was carried out in the Lambosir Block in the Gunung Ciremai National Park area in February - June 2022 using 5 traps, namely Butterfly net, Sweep net, Light trap, Aerial bait trap and Yellow Trap. using the total density, frequency and the Shanon Weiner Diversity Index. The results showed that on the land cover of shrubs, calliandra and mixed forests, 42 species of insects were found from 8 orders with 246 individual species with a diversity value of 3.18 or in the high category. The 8 orders found in 3 land covers included Coleoptera 4 species, Diptera 3 species, Hemiptera 4 species, Hymenoptera 4 species, Lepidoptera 23 species, Odonata 1 species, Orthoptera 2 species and Phasmatodea 1 species. In addition to the high diversity category, insects that exist in 3 land covers have various roles such as pollinators, decomposers, assisting ecological succession, bio indicators and predators. The correlation between land cover with the number of species and the number of individual species based on the Scatter plot has a correlation value of 91%. Keywords; Diversity, insect, conservation, rehabilitation zone, Lambosir